How do users adopt health information from social media? The narrative paradigm perspective. Issue 3 (September 2019) - Li, Jia; Tang, Jie; Liu, Xuan; Ma, Ling
Introduction: A recent trend in health information seeking and sharing is the use of social media. Although there are several benefits to the use of social media for health communication, the quality of health information exchanged on social media is troubling due to its informal, unregulated mechanisms for information collection, sharing and promotion. Therefore, it is important to understand how users adopt health information from social media. Method: Considering the user-generated and storytelling nature of social media messages, this research employed the narrative paradigm perspective to explain the social media health information adoption phenomenon. Specifically, narrative coherence (NC) and narrative fidelity (NF) were hypothesised to have positive effects on the intention to adopt (IA). Additionally, socio-economic status (SES) was viewed as a proxy variable to cognitive capability and was hypothesised to moderate the effects of NC and NF. A scenario-based survey was conducted to test the proposed research model. Results: We obtained a total of 257 valid questionnaires. The results indicated that NF ( p < 0.001) had a positive effect on the IA social media health information. The NC ( p < 0.01) had no impact on the low SES users but a positive impact on the high SES users. Further, the effect of NF ( p < 0.01) on the IA was higher for high SES users than low SES users. Conclusions: NC and NF are two major driving forces in social media health information adoption, and the effect of both narrative paradigm variables depends on the SES users. Implications: Results of this study show how the narrative paradigm, with a focus on the storytelling method of communication rather than logical scientific argument, can not only explain the uptake of health messages from social media, but also provide guidance as to how to create health messages on social media that more effectively target end users.